The Humanistic rebellion and the Socratic education in Albert Camus - Ramírez Medina, Ángel (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The article departs from the analysis about the problem of evil in Camus, in dialogue with the answers given by the Greek gnosticism and the Christianity. In this context we speak about the failure of the theodicies, example of what Camus considers the «metaphysical rebellion». Next, we think about two existential categories (time and silence) which constitute counter-arguments faced with the condemnation of the human nature from the most orthodox versions of the Christianity and the rationalist philosophies. Camus makes an anthropodicy speech whose main idea is a humanist, transforming rebellion, limited in its praxis and aspirations for moral values generated by itself, which confer a relative sense to the existence. The article ends with a reflection about education as a powerful resource of social transformation.